Effects of water-based citric acid on growth performance and water disappearance of weanling pigs - R O Gottlob; C N Groesbeck; J M DeRuochey; C R Neill; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
A total of 399 weanling pigs (initially 12.2 lb and 14 ± 3 d of age, PIC) were used to determine the effects of water-based citric acid on nursery pig growth performance and water disappearance. Pigs were given a common diet and one of two experimental water treatments: 1) negative control, water containing no additives; and 2) water containing 0.55 g per L citric acid. Overall (d 0 to 10 after weaning), there were no differences in growth performance between pigs provided water or water with added citric acid. In addition, water disappearance was similar between treatments for the overall period. These results suggest that adding 0.55 g/L of citric acid improves neither pig growth or water intake when offered immediately after weaning.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Citric acid; Nursery pig; Water; Growth; Swine